A RXR Ligand 6-OH-11-O-Hydroxyphenanthrene with Antitumour Properties Enhances (−)-Epigallocatechin-3-gallate Activity in Three Human Breast Carcinoma Cell Lines. (11th June 2014) - Farabegoli, Fulvia; Govoni, Marzia; Ciavarella, Carmen; Orlandi, Marina; Papi, Alessio
Abstract : (−)-Epigallocatechin-3-gallate (EGCG) and chemotherapeutic agents cotreatment can improve cytotoxicity against cancer cells. We showed that EGCG and the rexinoid 6-OH-11-O-hydroxyphenanthrene (IIF), given together, were cytotoxic toward MCF-7, MCF-7TAM, and MDA-MB-231, three breast carcinoma cell lines showing different molecular characteristics. Cell growth arrest and apoptosis were greater after EGCG and IIF cotreatment than after individual administration. Cytotoxicity was related to upregulation of 67-kDa laminin receptor (LR67), one of the principal molecular targets of EGCG, and activation of the nuclear retinoic X receptors (RXRs) pathway. Furthermore, the transcription factor Forkhead box O3 (Foxo3a), a protein able to trigger apoptosis through upregulation of genes necessary for cell death, was activated. EGCG and IIF cotreatment produced a significant nuclear import of Foxo3a from the cytoplasm in MCF-7, MCF-7TAM, and MDA-MB-231 cells. In MCF-7TAM cells only, Foxo3a nuclear localization was associated with p473AKT downregulation. For the first time we showed that when EGCG and IIF, two harmless molecules, were given together, they might increase cytotoxicity in three breast carcinoma cell lines, two of them being representative of poorly responsive breast carcinoma types.